The Use of GPR in Delineating an Iron Sand Boundary and the Determination of Its Electromagnetic Wave Velocity: A Case Study in Jepara, Central Java - Bijaksana, S.; Rusyanti, I.; T. Taib, M. I.; Pasasa, L. A.; Andreas, A. S. (ITB Journal Publisher, LPPM ITB, 2005)
Â Exploring the vertical extent of iron sand deposit is challenging as conventional geophysical methods (electrical resistivity, geomagnetic, and seismic refraction) are inappropriate and unsuccessful in delineating the iron sand deposit from the bedrock. Ground-penetrating radar (GPR) offers a solution to the above problem as radar is not affected negatively by the physical properties of iron sand. In the year 2003, a RAMACâs GPR survey was carried out in the coast of Bayuran in the Regency of Jepara, Central Java to map the distribution of sub-bottom iron sand. The sand is highly magnetic. The survey used 100 MHz antennas. The survey is also complimented by a novel method in determining the electromagnetic (EM) wave velocity of iron sand. Combination of reflection profiling and CMP sounding was deployed. Results of CMP sounding were processed using CMP-semblance analysis that produces the RMS velocity in velocity-time spectra. The RMS velocity is then converted to interval velocity using Dixâs formula and is found to be about 135 mm/ns. Meanwhile, combination of magnetic susceptibility, relative permittivity, and dissipation factors produces radiowaves velocity of iron sand as a function of frequency. The velocities of radiowaves estimated from laboratory match that estimated from CMP analysis.